Analysis Of The Relationship Of Rare Earth Elements To Magnetic Mineral Concentrations In Pumice Around Sigura-Gura - Dian Laila Fitri; Hamdi Hamdi; Ahmad Fauzi; Letmi Dwiridal (Journal of Experimental and Applied Physics, 2023)
Rare earth elements are part of one of the strategic minerals and are included in the "critical minerals". Concentrations of rare earth elements are economically precious deposits that can be used as mining commodities. Pumice is the result of volcanic eruptions and it is one of the minerals containing the rare earth elements, one of which is found in Sigura-Gura, North Sumatra. The research aims to determine the composition of rare earth elements, the relationship between rare earth elements and magnetic mineral concentration, and to determine the concentration of magnetic minerals in pumice in Sigura-gura. The method employed is rock magnetic method with Bartington Magnetic Susceptibility Meter Sensor type B (MS2B), and X-Ray Fluorescence (XRF). Results indicated that Sigura-Gura pumice samples, and Sigura-Gura Waterfall have quite varied magnetic mineral concentrations with a range of values from 111,3 x 10-8m3/kg to 349,9 x 10-8m3/kg, with antiferromagnetic magnetic properties and grain types with almost no SP grains. Samples of Sigura-Gura pumice contain elements of Eu, Ce, and Y, while samples from Sigura-Gura Waterfall contain elements of Eu and Y. There is a correlation between the amount of magnetic minerals and rare elements, and the more elements are present in a sample, the lower the value that is produce, and the greater the percentage of elements obtained, the smaller (%) is obtained.